Sugar palm tree: Potential and future prospect in Malaysian traditional cuisines / Nur Suraya Abdullah and Noorshilawati Abdul Aziz - Abdullah, Nur Suraya; Abdul Aziz, Noorshilawati (2015)
The use of palm sugar in Malay traditional cuisines is popular among the Malay and it has natural sweetness which can create a difference in the taste of food. Sugar palm seeds can be used to make juices and sweets. This plant also has high economic value and potential as a substitute for brown sugar. Its fermented juice or nira can be used as a beverage and have potential as biofuel. However, not all traders use palm sugar in the preparation of their dishes because it is expensive and difficult to obtain. Palm tree is not commercially planted due to the difficulty of seeds to germinate. Many sugar makers get material from trees that grow around the village. So, it leads to a lack of continuous supply of sugar caused by limited number of trees for tapping. The difficulty of this plant to grow is because of the dormancy of the seeds which may take more than a year to germinate. Typically, many methods can be practiced to overcome seed dormancy, either by mechanical or chemical techniques. The use of biotechnology such as tissue culture also is a promising technique in production of higher number of plantlets in short time. Thus, the main purposes of this article are to discuss the potential and future prospects for palm trees in Malaysian cuisines and to identify various methods to overcome dormancy of sugar palm seed.